The Injected Plasma of Myasthenia Gravis Patient with A Low T-reg Level Caused Clinical Myasthenic Syndromes in Swiss-Webster Mice - Pasmanasari, Elta Diah; Purwaningsih, Erni Hernawati; Retnaningsih, Retnaningsih; Purba, Jan Sudir; Octaviana, Fitri (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Myasthenia gravis (MG) is a rare autoimmune disease affecting neuromuscular junction involvement. The finding that T-reg level in MG patients was lower than that in normal persons leads to the idea that the primary pathology of the disease is T-reg dependent. The T-reg level of MG patients seems to be decreasing compared to that of normal persons. The study was conducted to observe the contribution of T-reg level in plasma injected into Swiss-Webster mice to develop clinically and pathologically myasthenic syndromes.METHODS: Swiss-Webster mice were grouped into three groups: the groups received plasma with normal, low, and high T-reg levels, respectively. The T-reg levels of the mice were measured with flow cytometry analysis and a human regulatory T-cell cocktail for T-cell surface cell marker. The motor function, interleukin (IL)-2, interferon (IFN)-γ, and thymus weight of mice were measured after the injection. Histopathological examination was performed to analyze mice’s muscles and thymus.RESULTS: The result identified that the motor function (2-week treatment group: p=0.021 and 3-week treatment group: p=0.032) and muscle width (p=0.014, p=0.032 and p≤0.001) were significantly lower in the low T-reg level plasma group compared to control and high T-reg level plasma groups. The thymus showed an increase in weight without an increase in the cortex-medulla ratio of the thymus, indicating hyperplasia. Both IL-2 and IFN-γ levels were lower in the low and high T-reg level groups compared with the control group, indicating the autoimmune process.CONCLUSION: Low T-reg level was associated with lower motor function, muscle width, increased thymus weight, as well as lower IL-2 and IFN-γ levels. T-reg level contributed to clinical myasthenic syndromes but not pathological findings. This research method is expected to be a basis for the development of animal models with Swiss-Webster mice.KEYWORDS: animal model, Myasthenia gravis, Swiss-Webster mice